1997
DOI: 10.1063/1.118672
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanosized silver particles in ion-exchanged glass by electron beam irradiation

Abstract: Ag particles of 4.2 nm mean diameter have been formed inside a glass matrix, doped with silver by ion exchange, by electron beam irradiation of the glass cut into thin slices by ultramicrotomy. By this treatment, a high concentration of particles which are homogeneously arranged throughout the glass and exhibit a narrow size distribution is achieved ͑volume fraction of particulate silver: 3.5 ϫ10 Ϫ2). The interface stress reflecting the particle/matrix interaction is comparable to that of isolated Ag particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 19 publications
6
48
0
3
Order By: Relevance
“…Irradiation processing was performed in a conventional TEM (EM 10 CR) using an extraordinary large beam current density of 6.4 A=cm 2 at 100 kV acceleration voltage [12,16]. Before this processing, the glass was cut into 30 nm thick slides using an ultramicrotome to allow uniform interaction with the electron beam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation processing was performed in a conventional TEM (EM 10 CR) using an extraordinary large beam current density of 6.4 A=cm 2 at 100 kV acceleration voltage [12,16]. Before this processing, the glass was cut into 30 nm thick slides using an ultramicrotome to allow uniform interaction with the electron beam.…”
Section: Methodsmentioning
confidence: 99%
“…Ion irradiation enables redistribution of pre-formed particles [9] and mixing of insulator-metal layer compounds to get particulate composites [10,11]. Ionising radiation like X-ray or electron beams cause reduction of metal ions contained in glass [12,13]. Laser irradiation may induce redox reactions by local heating [14], or cause various morphological changes by utilising the localised spectral absorption of pre-existing particles [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the E-beam irradiation increased the diffusivity of atoms by several orders of magnitude compared to that in the therm a l t r e a t m e nt s t e p du r i ng s y nt h e s i s . T he precipitation of nanoparticles occurs not only at distinctly lower temperatures, but also at considerably higher rates in the irradiation process [10,12]. This demonstrates that the E-beam irradiation can lead to a fast grain growth of the primary TiO 2 nanoparticles, resulting in a bigger smallest particle size.…”
Section: Resultsmentioning
confidence: 91%
“…However, most TiO 2 nanoparticles synthesized by the hydrolysis reaction exhibit a wide particle size distribution which is often inhomogeneous with respect to the location inside the electrode and leads to nonuniform electrochemical performance [7]. Herein, we introduce a new synthesis method to prepare the TiO 2 nanoparticles of a narrow particle size distribution as well as a homogeneous dispersion throughout the electrode, which can be achieved by electron beam (Ebeam) irradiation during the synthesis process [10][11][12]. The E-beam irradiation has been used to induce graft polymerization or cross-linking of various separators for Li-ion-batteries to enhance electrochemical performances because the high density of the E-beam can create a large amount of radicals over entire polymer samples [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ion irradiation enables redistribution of pre-formed particles and mixing of insulator-metal layer compounds to get particulate composites [6][7][8]. Ionizing radiation like X-ray or electron beams causes reduction of metal ions contained in glass [9,10]. Ion irradiation causes liberation of electrons, holes or displacement of lattice atoms or change in network structure.…”
Section: Introductionmentioning
confidence: 99%